Analisis Konseptual Pembelajaran Jarak Jauh: Tinjauan Pustaka Tentang Kelebihan, Kekurangan, dan Tantangan di Era Digital - Vina Nailil Afida; Ikfina Ilma Salwa; Riza Faishol (Jurnal Wahana Literasi Pendidikan, 2026)
This scientific article analyzes the concept of distance learning in the digital era through a systematic literature review, focusing on an integrated identification of its advantages, disadvantages, and challenges. This research uses a library research method with a descriptive qualitative approach, synthesizing various recent primary and secondary literature. The results show that distance learning offers main advantages in the form of flexibility of time and place, cost efficiency, and expanded access to digital learning resources. However, these advantages are offset by disadvantages such as reduced direct social interaction, high demands for self-motivation, and shifts in the roles and workloads of educators. Furthermore, the implementation of distance learning in Indonesia still faces systemic challenges such as the digital divide, uneven digital literacy, and difficulties in maintaining the quality and integrity of online learning. The novelty of this article lies in the triadic synthesis that links these three dimensions in one comprehensive analytical framework, with an emphasis on the post-pandemic Indonesian context. The implication is that the effectiveness of distance learning requires a holistic ecosystem approach, including equitable infrastructure, strengthening educator capacity, implementing contextual hybrid learning models, and active involvement of parents and the community. Thus, this article provides a conceptual contribution to the development of more inclusive, adaptive, and sustainable distance learning policies and practices in Indonesia.